Interleukin-8 as a Biomarker for Disease Prognosis of Coronavirus Disease-2019 Patients - Li, Lili; Li, Jie; Gao, Meiling; Fan, Huimin; Wang, Yanan; Xu, Xin; Chen, Chunfeng; Liu, Junxiao; Kim, Jocelyn; Aliyari, Roghiyh; Zhang, Jicai; Jin, Yujie; et al. (Frontiers in Immunology, 2021)
The widespread prevalence of coronavirus disease-2019 (COVID-19) which is caused by severe respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, has resulted in a severe global public health emergency. However, there are no sensitive biomarkers to predict the disease prognosis of COVID-19 patients. Here, we have identified interleukin-8 (IL-8) as a biomarker candidate to predict different disease severity and prognosis of COVID-19 patients. While serum IL-6 become obviously elevated in severe COVID-19 patients, serum IL-8 was easily detectible in COVID-19 patients with mild syndromes. Furthermore, lL-8 levels correlated better than IL-6 levels with the overall clinical disease scores at different stages of the same COVID-19 patients. Thus, our studies suggest that IL-6 and IL-8 can be respectively used as biomarkers for severe COVID-19 patients and for COVID-19 disease prognosis.